A randomized clinical study to compare postoperative pain relief in ilioinguinal nerve block versus transversus abdominis plane block following inguinal hernia repair surgery - Jay Kumar Kolewar; Jitendra Agrawal; Sourabh Shrivastava; Isha Jain; Preeti Goyal (Asian Journal of Medical Sciences, 2023)
Background: Inguinal hernia surgeries are associated with postoperative pain and discomfort. Transversus abdominis plane (TAP) block and Ilioinguinal/Iliohypogastric (IIIH) nerve blocks are widely used to control postoperative pain. In this study we have compared postoperative pain relief between TAP block and IIIH nerve block in the patients undergoing inguinal hernia surgery under spinal anesthesia. Aims and Objectives: The primary aim of this study was to compare postoperative pain relief of TAP block and IIIH block in patients undergoing inguinal hernia surgery. Secondary objectives were to observe hemodynamic parameters and to observe for postoperative side effects if any. Materials and Methods: Sixty patients of age group 18–65-year-old males, ASA grade I, II, were randomised into two groups TAP group (n=30) and IIIH group (n=30). TAP group received 30 mL of 0.25% ropivacaine TAP block and group IIIH received 20 mL, and wound infiltration with 10 mL of 0.25% ropivacaine. Duration of analgesia was recorded, visual analogue scale (VAS) score compared in first 24h postoperatively. Perioperative haemodynamic parameters were recorded. Results: VAS score was found significant at 1, 2, 3, 4, 5, 8, 10, 16 h (P<0.001). The mean duration of analgesia was found to be 4.64±1.16 h and 6.3±1.84 h for IIIH group and TAP group respectively which was statistically significant (P<0.001). Haemodynamic were stable and no complication was there in both the groups. Conclusion: As a part of multimodal analgesia regimen both TAP block and IIIH block provided good pain relief postoperatively in patients undergoing inguinal hernia. In this study TAP block provided prolonged pain relief than IIIH block after inguinal hernia repair.